Treatment of pulmonary arterial hypertension in connective tissue disease - Grünig, Ekkehard (Drugs, 2012)
Pulmonary arterial hypertension (PAH) is a group of distinct disorders that includes idiopathic PAH (IPAH), familial PAH and PAH associated with other conditions (APAH) such as connective tissue disease (CTD-APAH) or congenital heart disease. PAH is characterized by increased pulmonary arterial pressure and pulmonary vascular resistance. If left untreated, PAH can lead to right heart failure and premature death. CTD-APAH rep-resents an important clinical subgroup of APAH that has a higher risk of death than IPAH. The European treatment guidelines advocate the use of PAH-targeted therapies including bosentan, ambrisentan, sildenafil, inhaled iloprost, intravenous epoprostenol (I-A recommendations), tadalafil or treprostinil (I-B recommendations) for patients in WHO functional class II-III. Not all randomized clinical studies of the approved PAH-targeted therapies have included patients with CTD-APAH. The purpose of this review is to describe the clinical characteristics of CTD-APAH and discuss the approved pharmacological treatments, with a focus on data specific to this subgroup where possible.
First online: 10 December 2012
Gesehen am 22.06.2018